Social Capital: an Efficient Instrument for Sustainable Development (Algeria 1990 -2012) - Diab Zeggai; Bensekrane Boudali (European Scientific Journal, ESJ, 2016)
The studies on the development and well-being focused on the tools and the instruments and declaration of economic reforms which accelerated significantly to put civil society under study and look after stages of the experiment and application, where after the first generation of reforms during the period [1980-1988], what are known as financial restructuring and organic and structural adjustment programs, which support the orientation to a market economy; then the second generation of reforms [1990-1996] on the government’s work in order to define the impact and effectiveness on economic activity. Finally, the last generation came on the role of civil society, that considering the networks, trust and participation become a major research under the title of "social capital".